MENINGKATKAN KEMAMPUAN KERJA SAMA SISWA PADA MATEMATIKA KELAS V MENGGUNAKAN MODEL BERSAMA DI SEKOLAH DASAR - Jamilatur Rahmah; Fathul Jannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aimed to improve students' collaboration skills in Mathematics learning through the implementation of the BERSAMA model, which was a combination of Problem-Based Learning, Group Investigation, and Make a Match. The study was motivated by the low level of students' collaboration skills, which resulted from one-way, teacher-centered instruction and a lack of enjoyable learning experiences. This research was a Classroom Action Research (CAR) with a qualitative approach, conducted over four sessions in fifth grade of state elementary school Teluk Tiram 5 Banjarmasin during the even semester of the 2024/2025 academic year. Data were collected through observations of students’ classroom activities and were analyzed using descriptive qualitative and quantitative methods, employing percentage calculations. The findings showed a significant improvement in students’ collaboration skills, increasing from 44% to 100%, categorized as “very capable,” after the application of the BERSAMA model. The study concluded that the BERSAMA model was effective in enhancing students’ collaboration skills and could serve as an alternative instructional model that promotes active and collaborative participation in Mathematics learning.